2017
DOI: 10.1186/s12889-016-3938-4
|View full text |Cite
|
Sign up to set email alerts
|

Taxing sugar-sweetened beverages: impact on overweight and obesity in Germany

Abstract: Background: Consumption of sugar-sweetened beverages (SSBs) increases the risk of overweight and obesity. Taxing SSBs could decrease daily energy consumption and body weight. This model-based study evaluated the impact of a 20% SSB-sales tax on overweight and obesity in the context of Germany.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 35 publications
(49 reference statements)
4
49
0
5
Order By: Relevance
“…In a model constructed with the aid of data available from Germany it was shown that the potential introduction of 20% taxes on sugared drinks could decrease the caries burden in the German population and make considerable savings in the economy through the reduction of dental treatment expenditure as well as the additional tax revenue, while it would also result in lower inequalities in dental caries [Schwendicke et al, 2016]. Beyond this effect, a reduction of the obesity rate was also shown to be possible in Germany [Schwendicke and Stolpe, 2017]. Calculations using data from Israel, where sugar consumption on average represents 12% of the total energy intake, showed that a reduction of sugar consumption to 10% of the total energy intake as recommended by WHO could reduce the diabetes-related number of deaths by approximately 5% [World Health Organization, 2015;Schillinger and Kahn, 2017].…”
Section: Doi: 101159/000490951mentioning
confidence: 99%
“…In a model constructed with the aid of data available from Germany it was shown that the potential introduction of 20% taxes on sugared drinks could decrease the caries burden in the German population and make considerable savings in the economy through the reduction of dental treatment expenditure as well as the additional tax revenue, while it would also result in lower inequalities in dental caries [Schwendicke et al, 2016]. Beyond this effect, a reduction of the obesity rate was also shown to be possible in Germany [Schwendicke and Stolpe, 2017]. Calculations using data from Israel, where sugar consumption on average represents 12% of the total energy intake, showed that a reduction of sugar consumption to 10% of the total energy intake as recommended by WHO could reduce the diabetes-related number of deaths by approximately 5% [World Health Organization, 2015;Schillinger and Kahn, 2017].…”
Section: Doi: 101159/000490951mentioning
confidence: 99%
“…Furthermore, the authors found a more significant decrease in overweight and obesity prevalence among young people of lower-income households [68].…”
Section: In High-income Countriesmentioning
confidence: 96%
“…In the USA, PEs ranged from -0.79 to -1.00 [50,55]. In Germany, there was no country specific ownor cross-PE, thus the authors used PEs of -0.9 to -1.2 from a previously published article [68]. In Australia, own-and cross-PE was estimated using the Almost Ideal Demand System (AIDS) as -0.63 [64,65].…”
Section: Ssb Price Elasticities Of Demandmentioning
confidence: 99%
“…Für Deutschland gibt es bislang nur eine Modellrechnung für die Einführung einer zusätzlichen Steuer in Höhe von weiteren 20 % auf zuckergesüßte Getränke. Laut dieser Modellrechnung würde eine solche Steuer zu einer merklichen Reduktion der Adipositasprävalenz führen (-4 %), mit einem deutlich ausgeprägteren Nutzen für jüngere Männer (20 -29 Jahre) aus bildungsfernen Schichten (-22 %) [14].…”
Section: Wahl Lenken Durch Steuerunclassified